Optimum treatment regimens for Helicobacter pylori infection - Richard H Hunt (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
The treatment of Helicobacter pylori infection includes of current standard triple therapies consisting of a proton pump inhibitor, clarithromycin and amoxicillin or metronidazole on the basis of simplicity, safety, and efficacy. There are several factors determining the success of H. pylori eradication treatment. They include the components of a treatment regimen, the treatment duration, patient compliance, the presence of resistant or virulent strains of Helicobacter pylori and possibly the patient’s gastric acid secretory status. PPI, clarithromycin 500 mg, amoxicillin 1 g or metronidazol 400 mg, all given bid for 7 days are the most commonly used combination regimens. RBC-based triple therapies, furazolidone or rifabutin containing regimens can be used as an alternative approach to PPI-based triple therapies in areas where bacterial resistant strains of H. pylory are concerned.  Keywords: treatment, Helicobacter pylori, PPI,  clarithromycin, amoxicillin, metronidazole, PAM, PMC,  PAC, RBC